Teacher’s Facilitating Strategies in Conducting Science Investigatory Project - Jr, Gregorio Tabamo Llano; Borja, Emmylou Aspacio; Mutya, Romel Cayao (FKIP Universitas Lampung, 2023)
Teacher’s Facilitating Strategies in Conducting Science Investigatory Project.Objective: The study assessed the science teacher’s facilitating strategies in conducting the Science Investigatory Project (SIP) in the new normal in terms of formulating a problem, developing a design, and constructing an explanation. Methods: A descriptive-correlational research method was utilized using a survey questionnaire administered to 293 STEM students and 59 STEM research teachers. Findings: Findings revealed that teachers have agreed that the facilitating strategies in conducting SIP in terms of formulating a problem, developing a design, and constructing an explanation have been practiced in the new normal setting. Students strongly agreed that the facilitating strategies had been mostly practiced by the teachers in the new normal. Conclusion: STEM teachers have adapted to the sudden shift in the educational system. They have been prepared with skills and have been practicing various facilitating strategies that have assisted students in conducting their SIPs in the new normal. Keywords: facilitating strategies, research, science investigatory project.DOI: http://dx.doi.org/10.23960/jpp.v13.i1.202307